2022
DOI: 10.3390/metabo12090829
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum and Placental Metabolomes in Association with Prenatal Phthalate Exposure and Neurodevelopmental Outcomes in the MARBLES Cohort

Abstract: Prenatal exposure to phthalates, a family of endocrine-disrupting plasticizers, is associated with disruption of maternal metabolism and impaired neurodevelopment. We investigated associations between prenatal phthalate exposure and alterations of both the maternal third trimester serum metabolome and the placental metabolome at birth, and associations of these with child neurodevelopmental outcomes using data and samples from the Markers of Autism Risk in Babies Learning Early Signs (MARBLES) cohort. The thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…We were particularly interested in the one-carbon metabolism pathway because our previous study found that OC mothers had alterations in the levels of metabolites in this pathway compared to LC mothers ( 22 ), and others have also found an association between perturbations in this pathway and adverse neurodevelopmental outcomes ( 40 , 41 ). The impact of calorie restriction in mothers with obesity was apparent ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…We were particularly interested in the one-carbon metabolism pathway because our previous study found that OC mothers had alterations in the levels of metabolites in this pathway compared to LC mothers ( 22 ), and others have also found an association between perturbations in this pathway and adverse neurodevelopmental outcomes ( 40 , 41 ). The impact of calorie restriction in mothers with obesity was apparent ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Samples were prepared for metabolomics analysis by thawing on ice and subsequently subjected to ultrafiltration centrifugation to remove protein using Amicon Ultra-0.5 mL 3000 MW centrifugal filters (Millipore), as described elsewhere. 14 For maternal serum, filtrate volume was adjusted to 207 μL with ultrapure water if an insufficient sample was collected, and an internal standard, containing 5.0 mmol/L 3-(trimethylsilyl)-1-propanesulfonic acid-d6 (DSS-d6), 0.2% sodium azide, and 99.8% deuterium oxide (Chenomx) was added. For umbilical cord serum, filtrate volumes were measured, and filtrates were frozen, dried using a miVac concentrator system (Genevac), and reconstituted using 240 μL of 10 mmol/L potassium phosphate buffer prepared in deuterium oxide to improve signal-to-noise.…”
Section: Methodsmentioning
confidence: 99%
“…143−145 Placental metabolome related to maternal obesity 146 or associated with neurodevelopmental outcomes has also been investigated. 147 Although each condition study makes comparison with placentas from uncomplicated, healthy "control" pregnancies, the placental metabolome related to these normal pregnancies remains globally understudied. 148 In these studies, differences in several metabolic pathways (energy balance, catabolism, oxidative stress) between groups are often pronounced and statistically distinguishable.…”
Section: Implementation Of Innovative Biomonitoring Methods To Deciph...mentioning
confidence: 99%
“…The majority of studies focused on the pathophysiology of placental diseases to identify differentiating endogenous biomarkers associated with pregnancy complications such as fetal growth restriction (FGR), spontaneous preterm birth (SPTB), gestational diabetes mellitus (GDM), or preeclampsia. Placental metabolome related to maternal obesity or associated with neurodevelopmental outcomes has also been investigated . Although each condition study makes comparison with placentas from uncomplicated, healthy “control” pregnancies, the placental metabolome related to these normal pregnancies remains globally understudied .…”
Section: Implementation Of Innovative Biomonitoring Methods To Deciph...mentioning
confidence: 99%